The European Grouping of Territorial Cooperation (EGTC): A New Tool Facilitating Cross-Border Cooperation and Governance - Zapletal, Jirka (Quaestiones Geographicae, 2010)
The European Union is becoming one undivided continent where territories are faced with borderless economic, social and environmental challenges while still being governed within traditional institutional boun-daries. Integration raises the question of cohesion among different territories, and territorial cohesion is a new objective for the Union according to the Lisbon Treaty. Cooperation between territories, beyond frontiers and across different institutional layers, is becoming crucial for providing multi-level governance to new functional regions. The European Grouping of Territorial Cooperation (EGTC), a new legal and governance tool established by Regulation 1082/2006, was conceived as a substantial upgrade for this multi-level governance and beyond-the-border cooperation. Four years after its adoption, a number of EGTCs have been set up, and new ones are in the pipeline. Recently the European Commission and the Committee of the Regions have launched a consulta-tion with the aim to review the existing legislation since 2007 on the EGTC and adjust it if necessary. The results are to be presented this year in Brussels during the 8th edition of the Open Days. The article ﬁrst highlights the EGTC framework in support of integration at a regional level and shows the background of the regulation. It then focuses on the legal issues involved, such as legal personality, potential members, tasks, organisation, state control, and liability of an EGTC. After showing the implementation status of a national EGTC, the article closes with further steps to be taken.